External Drivers of E-Wallet Continuance and Loyalty Among Mid-to-Late Adulthood Consumers in Indonesia - Widyoretno Adiani (Research Synergy Foundation, 2021)
The rapid growth of digital payments in Southeast Asia, particularly Indonesia, has transformed financial behaviors, yet significant adoption and usage gaps remain among mid-to-late adulthood consumers. This study investigates the determinants of e-wallet continuance usage and loyalty within this mid-to-late adulthood segment in Indonesia, here referring to individuals aged 40 years and above, a demographic increasingly important to the nation’s digital economy. Drawing on Expectation Confirmation Theory and supported by insights from technology adoption and institutional perspectives, the research examines the influence of government support, social influence, and network externalities on continuance usage, and the role of continuance usage in shaping loyalty. Using a quantitative, cross-sectional design, data were collected from 223 e-wallet users within the targeted age segment and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that government support and social influence positively predict continuance usage, underscoring the importance of institutional legitimacy and interpersonal cues in reinforcing digital payment engagement among mid-to-late adulthood consumers. In contrast, network externalities do not significantly influence continuance usage, suggesting that market-wide adoption cues play a limited role for this demographic. The results also confirm that continuance usage strongly predicts loyalty, highlighting the importance of sustained user experience in fostering long-term commitment to e-wallet platforms. Collectively, these insights offer theoretical contributions to fintech continuance literature and practical implications for strengthening digital inclusion and user retention among older consumers.